2020
DOI: 10.1016/j.transci.2019.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemoglobin and hematocrit levels at 1, 4 and 24 h after red blood cell transfusion

Abstract: Previous studies have shown that equilibration following a red cell transfusion had occurred by 24 h. A shorter time to follow the hemoglobin (Hb) and hematocrit (Hct) after transfusion may help physicians to provide earlier and more pertinent treatment. This was a prospective study conducted from December 2014 to August 2015. This research aimed to determine the equilibration time point of the level of Hb and Hct after one unit red blood cell (RBC) transfusion. Patients were randomized into three groups and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These need to be further studied with a larger sample size in the future We have also considered indicators, such as postoperative HGB, HGB loss should be considered for risk factors of HBL. Further, we found that HGB and Hct have a very close relationship [44]. When HGB changes, Hct will change with it.…”
Section: Discussionmentioning
confidence: 53%
“…These need to be further studied with a larger sample size in the future We have also considered indicators, such as postoperative HGB, HGB loss should be considered for risk factors of HBL. Further, we found that HGB and Hct have a very close relationship [44]. When HGB changes, Hct will change with it.…”
Section: Discussionmentioning
confidence: 53%